THE INFLUENCE OF LIVELIHOOD RESOURCES AND AGROECOLOGY PRINCIPLES ON THE SUBJECTIVE WELFARE OF COFFEE FARMERS IN THE BUKIT DAUN COMMUNITY FOREST, REJANG LEBONG DISTRICT - Riska Delfiyanti; Septri Widiono; Netta Agusti; Rizka Amalia Nugrahapsari (Agrisaintifika: Jurnal Ilmu-Ilmu Pertanian, 2026)
Coffee farming under the community forestry (HKm) scheme plays an important role in supporting rural livelihoods; however, improving farmers’ welfare requires sustainable management strategies that are ecologically and socio-economically integrated. This study analyzes the influence of livelihood assets on the implementation of agroecological principles and their implications for the subjective well-being of coffee farmers in the HKm area of Bukit Daun Protected Forest, Rejang Lebong Regency. The research employs a quantitative approach using descriptive analysis and Structural Equation Modeling–Partial Least Squares (SEM-PLS), with a sample of 96 HKm coffee farmers. The results show that livelihood assets and agroecological principles affect subjective well-being, where human capital has a significant influence on the implementation of agroecology. Furthermore, agroecology has a positive and significant effect on subjective well-being and acts as a mediating variable in the relationship between natural capital and subjective well-being. Meanwhile, physical, financial, human, and social capital do not have a direct significant effect on subjective well-being. These findings emphasize that improving farmers’ welfare is not solely determined by the ownership of livelihood assets but largely depends on the ability to transform these assets particularly natural capital through the implementation of sustainable agroecological practices. Keywords: Livelihood Assets, Agroecological Principles, Subjective Well-Being, SEM-PLS, HKm Coffee Farmers